THE SYMBOL OF LIFE BASED ON WILLIAM CARLOS WILLIAMS’S POEM, "SPRING AND ALL" THROUGH STILISTIC VIEW - Jumino Jumino (Sabda: Jurnal Kajian Kebudayaan, 2017)
"Spring and All" poem talks about life around us as a simple daily experience, describing the turn of the winter to the coming of the next season, spring. Human life is always changing. Not always happy, symbolized by winter but also not forever suffering, symbolized by spring. Natural suffering is usually a test to achieve happiness. Williams changes his choice of words between two parts of the poem to give the reader a different feeling in the poem that provides a contrast to the ideas of life and death. Through "Spring and All", Williams wants to show the reader how the ideas of life and death can be seen through the transition from winter to spring. He uses dreary imagery (winter) to show sorrow and death, then uses imagery (spring) to live life and hope. Thus, if people think positively, there will be opportunities to improve in the future.